2022
DOI: 10.1101/2022.09.07.22279692
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Robustness of SARS-CoV-2 Whole-Genome Sequencing from Wastewater with a Nonselective Virus Concentration Method

Abstract: The sequencing of human virus genomes from wastewater samples is an efficient method for tracking viral transmission and evolution at the community level. However, this requires the recovery of viral nucleic acids of high quality. We developed a reusable tangential-flow filtration system to concentrate and purify viruses from wastewater for whole-genome sequencing. A pilot study was conducted with 94 wastewater samples from four local sewersheds, from which viral nucleic acids were extracted, and the whole gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Similarly, targeted/MF increased the number of vertebrate viral families detected by more than half in both M and O WWTP samples as compared to samples that were targeted and directly extracted (targeted/DE), 80% (n= 4) and 67% (n=6), respectively (Figure S4). Similarly, Segelhurst et al, 2022 used a tangential-flow filtration method to recover 53% more complete or near complete SARS-CoV-2 genomes from wastewater samples as compared to concentration using precipitation. Still, a previous study by Hjelmsø et al, 2017 evaluated the impact of polyethylene glycol precipitation (PEG), skimmed milk flocculation, glass wool filtration, and monolithic adsorption filtration on the sequencing of viruses in wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, targeted/MF increased the number of vertebrate viral families detected by more than half in both M and O WWTP samples as compared to samples that were targeted and directly extracted (targeted/DE), 80% (n= 4) and 67% (n=6), respectively (Figure S4). Similarly, Segelhurst et al, 2022 used a tangential-flow filtration method to recover 53% more complete or near complete SARS-CoV-2 genomes from wastewater samples as compared to concentration using precipitation. Still, a previous study by Hjelmsø et al, 2017 evaluated the impact of polyethylene glycol precipitation (PEG), skimmed milk flocculation, glass wool filtration, and monolithic adsorption filtration on the sequencing of viruses in wastewater.…”
Section: Resultsmentioning
confidence: 99%
“…Segelhurst et al, 2022 used a tangential-flow filtration method to recover 53% more complete or near complete SARS-CoV-2 genomes from wastewater samples as compared to concentration using precipitation. 40 Still, a previous study by Hjelmsø et al, 2017 evaluated the impact of polyethylene glycol precipitation (PEG), skimmed milk flocculation, glass wool filtration, and monolithic adsorption filtration on the sequencing of viruses in wastewater. They demonstrated that concentration methods significantly impacted the detection of viruses in metagenomic sequencing reads with PEG-concentrated samples obtaining more viral-affiliated reads compared to the other methods.…”
Section: Targeted Metagenomics With Electronegative Membrane Filtrati...mentioning
confidence: 99%